2021
DOI: 10.22159/ijcpr.2021v13i1.40797
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Changes in Pregnancy Induced-Hypertension

Abstract: Objective: The aim is to determine the prevalence of retinal changes in Pregnancy Induced Hypertension (PIH) and its association with age, parity, proteinuria, blood pressureand severity of PIH. Methods: This is a tertiary hospital based Cross-Sectional study including all patients, clinically diagnosed with Pregnancy Induced Hypertension. General demographic details along with age, gravida, gestation period, proteinuria, blood pressure and severity of PIH were noted. Ophthalmic examination was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…In our study, severe hypertension was associated with retinopathy among women with hypertensive disorders of pregnancy. This finding is similar to what was reported in others studies 14 15 18 21 24. The retinal changes observed may be due to constriction of the retinal arterioles which occurs following the elevation of blood pressure 15.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, severe hypertension was associated with retinopathy among women with hypertensive disorders of pregnancy. This finding is similar to what was reported in others studies 14 15 18 21 24. The retinal changes observed may be due to constriction of the retinal arterioles which occurs following the elevation of blood pressure 15.…”
Section: Discussionsupporting
confidence: 92%
“…This is comparative to study done by Nathe et al showed among 23 patients with BP>160/100mmHg, 10 developed retinopathy. [11] In our study 2 cases (4.1%) present with papilledema. Exudative retinal detachment is rare in PIH.…”
Section: Discussionsupporting
confidence: 49%
“…Pregnancy-induced hypertension is the most frequent complication in pregnancy, increases the risk of mortality and morbidity for both the mother and the foetus. [2] According to WHO, 14% of maternal death are caused by hypertensive disorders in pregnancy. [3] Five to ten percent of pregnancies are complicated by hypertensive disorders.…”
Section: Introductionmentioning
confidence: 99%